Pemberdayaan Kesejahteraan Pelayanan Masyarakat - Cicilia Kimberly Oldy Saragih (Jurnal Pengabdian Masyarakat Nusantara, 2024)
This research aims to describe the role of mentors, inhibiting and supporting factors in mentoring the Community Service Welfare Empowerment Program. This research uses a qualitative approach, the companion is the research subject. The problem of poverty is a complex obstacle so that a country cannot have the ability to eradicate poverty alone. The majority of Indonesian people are at a low economic level, this causes the poverty rate in Indonesia to increase from year to year